Plan estratégico para el mejoramiento de los servicios educativos del área técnica de la unidad educativa "José María Velasco Ibarra" del cantón San Jacinto de Buena Fe, periodo 2014-2017 - Davila Morante, Irma Elisa (2016)
Education Unit "Jose Maria Velasco Ibarra" is a public educational institution providing knowledge, education and wisdom to each youth that comprise it. Today the institution offers the opportunity to train in technical careers such as marketing and sales, applications, management accounting, in order to improve the educational quality of the institution the following research entitled "STRATEGIC PLAN FOR IMPROVING presents EDUCATIONAL SERVICES TECHNICAL AREA OF EDUCATIONAL UNIT "José María Velasco Ibarra" CANTON SAN JACINTO IN GOOD FAITH, PERIOD 2014- 2017, since through a SWOT analysis of the current situation to explore the internal and external environment is determined the specialties of the technical area of the institution, the design of the organizational structure of the company was also performed by specifying the classification of the information thus selected to establish the background, history, mission, vision, corporate objectives the organizational chart setting strategies mean a change of continuous improvement in team work to strengthen the institutional and educational development, as results give quality education to young people today deserve in regard to technical careers that offer the educational unit "Jose Maria Velasco Ibarra ", for it is four operational development plans in which the strategic objectives, including mentioned are justified. Managing the growth of technological infrastructure upgrades in educational innovations, conduct training to students of the technical area of marketing and accounting and computer sales, motivate students in undertaking activities that contribute to society, this has as I aim to respond to needs that students of the institution.